Carbapenemase-producing Enterobacterales infections in COVID-19 patients. Issue 1 (2nd January 2022) - Pintado, Vicente; Ruiz-Garbajosa, Patricia; Escudero-Sanchez, Rosa; Gioia, Francesca; Herrera, Sabina; Vizcarra, Pilar; Fortún, Jesús; Cobo, Javier; Martín-Dávila, Pilar; Morosini, María Isabel; Cantón, Rafael; Moreno, Santiago
Abstract: Background: Carbapenemase-producing Enterobacterales (CPE) infections have been occasionally described in patients with coronavirus disease-19 (COVID-19). We assess the clinical features and outcome of these infections. Methods: In this retrospective single-centre, case-control study, we included 54 patients with CPE infection: 30 case-patients (COVID-19) and 24 controls (non-COVID-19), collected between March and May 2020. We compared the epidemiological, clinical features, and outcome between cases and controls. Results: CPE infection was more frequent in COVID-19 patients than in controls (1.1 vs. 0.5%, p = .005). COVID-19 patients were younger, had a lower frequency of underlying diseases ( p = .01), and a lower median Charlson score ( p = .002). Predisposing factors such as antimicrobial use, mechanical ventilation, or ICU admission, were more frequent in COVID-19 patients ( p < .05). There were 73 episodes of infection (42 cases and 31 controls) that were more frequently hospital-acquired and diagnosed at the ICU in COVID-19 patients ( p < .001). Urinary tract was the most common source of infection (47.9%), followed by pneumonia (23.3%). The frequency of severe sepsis or shock ( p = .01) as well as the median SOFA score ( p = .04) was higher in cases than in controls. Klebsiella pneumoniae (80.8%), Serratia marcescens (11%) and Enterobacter cloacae (4.1%) were the most common bacteria in both groups (KPC 56.2%, OXA-48 26% and VIM 17.8%). Overall 30-d mortality rate of COVID-19 patients and controls was 30 and 16.7%, respectively ( p = .25). Conclusions: COVID-19 patients have an increased risk of CPE infections, which usually present as severe, nosocomial infections, appearing in critically-ill patients and associated with a high mortality.